Draft Annual Plan 2008-2009 Volume-I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 2008)
Rajasthan, with a total geographical area of 3.42 lakhs Sq. km., is the largest State in the country. Administratively, Rajasthan is divided into 7 divisions and 32 districts, which are further sub-divided into 188 sub-divisions, 241 tehsils and 237 development blocks. The population of Rajasthan, standing at 5.65 crores (2001 Census) and a density of 165 persons per sq. km., recorded a decadal growth rate of 28.41 percent over the population of 4.40 crores (1991 Census) and a density of 129 persons per sq. km. The SC population in the State stood at 17.2 percent of the total and that of ST at 12.6 percent.
Government of Rajasthan, Planning Department